2003
DOI: 10.1055/s-2003-36600
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaktische Vakuumbiopsie mammographisch detektierter Läsionen - Erfolg, histologische Sicherheit, Patientenakzeptanz und BI-RADS™-korrelierte Indikationsoptimierung

Abstract: Vacuum-assisted breast biopsy is accurate, has a justifiable rate of histologic underestimation and is well accepted by patients. Patients with BI-RADS TM category 4 microcalcification benefit the most. Lesions of BI-RADS TM category 3 and BI-RADS TM category 5 should be biopsied only under special circumstances (family risk of breast cancer; assessment of lesions extension).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…7 Siegmann et al found in their study population of 166 stereotactic biopsies using a mammotome system (Breast Care, Ethicon Endo-Surgery, Norderstedt, Germany) that the histology of a sufficient vacuum-assisted biopsy was underestimated in 15% of their study population when compared with histology at excision. 15 Salem et al reported an overall underestimation rate of 9.6% for high-risk lesions and a DCIS underestimation rate of 19.2% for a hand-held vacuum-assisted stereotactic biopsy device (Vacora vacuum-assisted biopsy system, Bard, Tempe, USA) in a study population of 288 stereotactic biopsies. 12 Of the 13 cases of DCIS on SVAB in our study, 8 were followed with surgical excision, of which A factor that became evident from the present study is that many patients were not followed up with open biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Siegmann et al found in their study population of 166 stereotactic biopsies using a mammotome system (Breast Care, Ethicon Endo-Surgery, Norderstedt, Germany) that the histology of a sufficient vacuum-assisted biopsy was underestimated in 15% of their study population when compared with histology at excision. 15 Salem et al reported an overall underestimation rate of 9.6% for high-risk lesions and a DCIS underestimation rate of 19.2% for a hand-held vacuum-assisted stereotactic biopsy device (Vacora vacuum-assisted biopsy system, Bard, Tempe, USA) in a study population of 288 stereotactic biopsies. 12 Of the 13 cases of DCIS on SVAB in our study, 8 were followed with surgical excision, of which A factor that became evident from the present study is that many patients were not followed up with open biopsy.…”
Section: Discussionmentioning
confidence: 99%